AB1068 Ultrasound of salivary glands in sjogren's syndrome- which semi-quantitative scoring system is the best?. (15th June 2017) - Iorgoveanu, VC; Bojinca, V; Vlad, V; Mazilu, D; Saulescu, I; Groseanu, L; Opris, D; Balanescu, A; Constantinescu, C; Predeteanu, D; Ionescu, R
Abstract : Background: Sjogren Syndrome (SS) affects mainly exocrine glands. The latest diagnostic criteria designed for clinical studies are also used as guidance in clinical practice [1]. Ultrasonography (US) demonstrates specificity and sensibility in parotid and submandibular gland evaluation (SG). Parameters considered are echogenicity, homogeneity and margins regularity [1, 2, 3]. To standardize the assessment of B mode US of SG, different semi-quantitative scores were proposed. Objectives: To apply and compare 9 US semi-quatitative scoring systems in B mode scanning of salivary glands in Sjogren Syndrome. Methods: A research using keywords "salivary glands", "ultrasonograpy", "Sjogren Syndrome", "semi-quantitative score" in Medline/Pubmed was performed. There was a selection of most relevant articles. There were not considered relevant publications with impact factor <1. We performed the examination on SG in B mode US and applied these scores (De Vita, Niemela, Hocevar, Salaffi, Yukinori, Cornec, Theander) to our patients (primary and secondary SS). Results: Eighty four SG in patients diagnosed with primary and secondary (57.15%) SS were assessed. In the group of patients with SSA/SSB presence (85.7%), mean score was De Vita 1.78+/-1.21, Niemela 2.56+/-2.17, Hocevar and Wernicke 2.39+/-2.14, Salaffi 2.83+/-2.52, Yukinori 2.39+/-2.14, Milic 3.39+/-2.14, Cornec 1.78+/-1.215, Theander 1.28+/-0.752. Schirmer test and the need for using the artificial tears was correlated to SG alterations in scoring systems proposed by Niemela (r 0.465, p<0.05) and Salaffi ( r 0.496, p<0.02). All scoring systems were strongly correlated between them (r>0.8, p<0.01). Conclusions: Inhomogeneity of parenchyma was considered in all scoring systems. Others considered relevant glandular dimension and margins regularity [2, 3.4]. There was no difference between the scoring systems. Xeroftalmia valided through Schirmer test is correlated to SG parenchymal alterations. Our data is an update about semi-quantitative scoring systems in US of SG in SS. References: Vitali C, Bombardieri S, Jonsson R et al. Classification criteria for Sjögren's Syndrome: a revised version of the European criteria proposed by the American-European Consensus Group. AnnRheum Dis 2002;61:554–8. Makula E, Pokorny G, Palkό A.The place of magnetic resonance and ultrasonographic examinations of the parotid gland in the diagnosis and follow-up of primary Sjögren's syndrome. Rheumatology (Oxford). 2000;39(1):97–104. Niemelä RK, Takalo R, Hakala M. Ultrasonography of salivary glands in primary Sjogren's syndrome. A comparison with magnetic resonance imaging and magnetic resonance sialography of parotid glands. Rheumatology (Oxford). 2004 Jul;43(7):875–9. El Miedany YM, Ahmed I, El Gafaary M. Quantitative ultrasonography and magnetic resonance imaging of the parotid gland: can they replace the histopathologic studies in patients with Sjogren's syndrome? Joint Bone Spine.2004;71(1):29–38. Disclosure of Interest: None declared